Too much protection too little benefits: the case with copyright extension under the TPPA. - Ida Madieha, Abdul Ghani Azmi; Rokiah, Alavi (2015)

(untitled)
Malaysia is keen to sign the proposed Trans-Pacific Partnership Agreement in lieu of the increased business opportunities for trade in goods, services and investment among the twelve (12) member negotiating countries. The TPPA is expected to push for the adoption of copyright standards that are far more restrictive than the existing provisions in the Malaysian copyright law including the extension of copyright terms from life of the author + 50 years to life + 70 years for works created by individuals, and either 95 years after publication or 120 years after creation for corporate owned works (such as Mickey Mouse). This paper reports the preliminary findings of a research on the potential impact of copyright term extension on music industry in Malaysia. As Malaysia is an intellectual property user and net importer of intellectual property, it is feared that an extended term of copyright protection is likely to impede incentives for creation of new contents, increase the cost of licensing/royalties, diminish the choice and creativity of film and music industry and increase royalty payments flows abroad. The paper focuses on how suited is the proposed extension to the copyright core industries and how would the extension affect the growth and innovative capacity of these industries. Qualitative research methods will be utilized to obtain information and data to analyse the impact, particularly using in-depth interviews. Feedback from the respondents consisting of artists, recording companies, copywriters, copyright licensing bodies, and various associations that are related to creative content industry will be collected and collated in the paper. Secondary data from previous studies, government reports, industry and academic will also be used to support some of the main assertions in the paper. The paper suggests that there is not enough empirical evidence to support the notion that the extension will be economically advantageous to the country.